The diabetes drug liraglutide reverses cognitive impairment in mice and attenuates insulin receptor and synaptic pathology in a non‐human primate model of Alzheimer's disease. Issue 1 (2nd April 2018) - Batista, Andre F; Forny‐Germano, Leticia; Clarke, Julia R; Lyra e Silva, Natalia M; Brito‐Moreira, Jordano; Boehnke, Susan E; Winterborn, Andrew; Coe, Brian C; Lablans, Ann; Vital, Juliana F; Marques, Suelen A; Martinez, Ana MB; et al.
Abstract: Alzheimer's disease (AD) is a devastating neurological disorder that still lacks an effective treatment, and this has stimulated an intense pursuit of disease‐modifying therapeutics. Given the increasingly recognized link between AD and defective brain insulin signaling, we investigated the actions of liraglutide, a glucagon‐like peptide‐1 (GLP‐1) analog marketed for treatment of type 2 diabetes, in experimental models of AD. Insulin receptor pathology is an important feature of AD brains that impairs the neuroprotective actions of central insulin signaling. Here, we show that liraglutide prevented the loss of brain insulin receptors and synapses, and reversed memory impairment induced by AD‐linked amyloid‐β oligomers (AβOs) in mice. Using hippocampal neuronal cultures, we determined that the mechanism of neuroprotection by liraglutide involves activation of the PKA signaling pathway. Infusion of AβOs into the lateral cerebral ventricle of non‐human primates (NHPs) led to marked loss of insulin receptors and synapses in brain regions related to memory. Systemic treatment of NHPs with liraglutide provided partial protection, decreasing AD‐related insulin receptor, synaptic, and tau pathology in specific brain regions. Synapse damage and elimination are amongst the earliest known pathological changes and the best correlates of memory impairment in AD. The results illuminate mechanisms of neuroprotection by liraglutide, and indicate that GLP‐1 receptor activation may be harnessed to protect brain insulin receptors and synapses in AD. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.